594=(x+2)6x

Simple and best practice solution for 594=(x+2)6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 594=(x+2)6x equation:


Simplifying
594 = (x + 2) * 6x

Reorder the terms:
594 = (2 + x) * 6x

Reorder the terms for easier multiplication:
594 = 6x(2 + x)
594 = (2 * 6x + x * 6x)
594 = (12x + 6x2)

Solving
594 = 12x + 6x2

Solving for variable 'x'.

Reorder the terms:
594 + -12x + -6x2 = 12x + -12x + 6x2 + -6x2

Combine like terms: 12x + -12x = 0
594 + -12x + -6x2 = 0 + 6x2 + -6x2
594 + -12x + -6x2 = 6x2 + -6x2

Combine like terms: 6x2 + -6x2 = 0
594 + -12x + -6x2 = 0

Factor out the Greatest Common Factor (GCF), '6'.
6(99 + -2x + -1x2) = 0

Factor a trinomial.
6((9 + -1x)(11 + x)) = 0

Ignore the factor 6.

Subproblem 1

Set the factor '(9 + -1x)' equal to zero and attempt to solve: Simplifying 9 + -1x = 0 Solving 9 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -1x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -1x = 0 + -9 -1x = 0 + -9 Combine like terms: 0 + -9 = -9 -1x = -9 Divide each side by '-1'. x = 9 Simplifying x = 9

Subproblem 2

Set the factor '(11 + x)' equal to zero and attempt to solve: Simplifying 11 + x = 0 Solving 11 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + x = 0 + -11 Combine like terms: 11 + -11 = 0 0 + x = 0 + -11 x = 0 + -11 Combine like terms: 0 + -11 = -11 x = -11 Simplifying x = -11

Solution

x = {9, -11}

See similar equations:

| 37+4+-37+-5= | | 3+-8+-3+8= | | 9x+5=2*(5x-4) | | 35/50 | | 9x+5=2*5x-4 | | -1=3y-7 | | 9+-2+8+-9= | | 166=255-u | | 26=-4v+2(v+3) | | 9x+5=5x-4 | | 225=-w+85 | | -7+6+-4+-6= | | 75-w=219 | | 5+2+-5+6= | | 3x^2+4+5=0 | | x+71=y | | 3x^2+5x-6=x^2+x+8 | | 25+-17+2+-19+2+17+-33+19+-25+33= | | 9x^2-30x-25=48 | | 110=x+71 | | 100+30+15+20+-50+75+15+10= | | x=-142+3x | | 51-1/4= | | 43+-17+-19+17= | | 35+-15+-40+55= | | -3x^2-4x+5=3 | | x=51-1/4 | | (-7-3i)(-7+3i)= | | 2+-18+-2+10= | | 4x^3-2x^2-2x+1=0 | | 9+-4+3+-3= | | (8w+3)(5w-6)=0 |

Equations solver categories